2017
DOI: 10.1681/asn.2016101095
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor–1β Regulates Urinary Concentration and Response to Hypertonicity

Abstract: The transcription factor hepatocyte nuclear factor-1 (HNF-1) is essential for normal kidney development and function. Inactivation of HNF-1 in mouse kidney tubules leads to early-onset cyst formation and postnatal lethality. Here, we used Pkhd1/Cre mice to delete HNF-1 specifically in renal collecting ducts (CDs). CD-specific HNF-1 mutant mice survived long term and developed slowly progressive cystic kidney disease, renal fibrosis, and hydronephrosis. Compared with wild-type littermates, HNF-1 mutant mice exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…In addition to the formation of kidney cysts, HNF-1b mutant kidneys are characterized by increased interstitial fibrosis. 21 A similar phenotype is seen in humans with heterozygous mutations of UMOD, MUC1, REN, and SEC61A1, which has led to the recent nosology of ADTKD. 1 The resulting clinical manifestations include small kidneys, absence of significant hematuria or proteinuria, slowly progressive decline in GFR, and tubular abnormalities such as hyperuricemia, hypomagnesemia, and reduced urinary concentrating ability.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In addition to the formation of kidney cysts, HNF-1b mutant kidneys are characterized by increased interstitial fibrosis. 21 A similar phenotype is seen in humans with heterozygous mutations of UMOD, MUC1, REN, and SEC61A1, which has led to the recent nosology of ADTKD. 1 The resulting clinical manifestations include small kidneys, absence of significant hematuria or proteinuria, slowly progressive decline in GFR, and tubular abnormalities such as hyperuricemia, hypomagnesemia, and reduced urinary concentrating ability.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that collecting duct-specific deletion of HNF-1b using the Pkhd1/Cre deleter strain produces renal fibrosis. 21 To ablate HNF-1b in additional nephron segments, we generated kidney HNF-1b mutant mice using the Ksp/Cre deleter strain, which expresses Cre recombinase in all nephron segments and collecting ducts. 36 Trichrome staining showed that significant interstitial fibrosis was present in kidneys from Ksp/Cre;Hnf1b F/F mice at age 28 days (Supplemental Figure 5A).…”
Section: Hnf-1b Mutant Kidneys Develop Interstitial Fibrosis Through mentioning
confidence: 99%
See 2 more Smart Citations
“…following the instructions of the kit, then the cDNA was used for real-time quantitative-PCR analysis using PowerUp SYBR Green Master Mix (Applied Biosystems, USA) and ABI Prism 7500 (Applied 6 Biosystems, USA) according to the protocols provided by the kit [9]. The 2-ΔΔCT method was used to calculate the relative expression of target genes to GAPDH [10]. The primers used were as followed: University, China) were cultured as we previously reported [2].…”
Section: Real-time Quantitative-polymerase Chain Reaction (Pcr)mentioning
confidence: 99%